MANAGING CULTURAL DIVERSITY IN CLASSROOM – the case of Southwest Finland - Morcillo Soler, Irene (My University, 2020)
Finland has quickly grown in terms of immigration and consequently, the school population of the Finnish schools has had a fast transformation towards multicultural environments. As a result of this change, Finnish teachers face many challenges in their everyday work to support education for diversity. Therefore, this thesis aims to investigate how Finnish teachers manage cultural diversity in their classrooms. What pedagogic strategies do they use to embrace multicultural education and how if at all, their educational background prepared them for the present. Besides, the opinions of the teachers on how they think teaching educational programmes should improve towards education for diversity are collected. Ten teachers from nine different schools in Finnish basic education have been interviewed in this study, using as a case study the subregion of Turku in Southwest Finland. The results show that unless the Finnish Educational System is well prepared to cope with multicultural education, still some improvements need to be made from the educational policymakers to help teachers and students achieve the multicultural education aims.
Keywords: immigration; Education for diversity; Finnish Educational System; Multicultural Education.